Female Pediatrics Residency Program Directors: Position Length, Program Size, and Career Impact - Liam M. Courtney; Ankith G. Rao; Veronica Vuong; Avani Vaghela; Amanda Brooks; Gregg C. Lund (Women's Health Reports)
Background: Currently, the majority of pediatricians are female. However, it is unknown if that general representation is seen along the academic continuum. This study aimed to describe the sex distribution, position duration, and program size of pediatric residency program directors (PDs) and compare female PD representation to other roles along the academic continuum. Methods: Data from all 213 U.S. pediatric residency programs were obtained from publicly available sources. Female representation along the professional academic continuum is obtained from publicly available sources. PD position duration was divided into three groups: short (<5 years), medium (5–10 years), and long (>10 years). Program size was based on the total resident count: small (<31 residents), medium (31–60 residents), and large (<60 residents). Results: The majority of PDs, 153 (72%), were classified as female. Within each duration grouping, there were significantly more females than males. There was no significant difference in the within-sex distribution of duration grouping in the current PD position between female and male PDs. There were significantly more females than males in each program size group. The within-sex distribution of the program size grouping was not statistically different between female and male PDs. Females are less represented in academic positions with greater authority, such as pediatrics department chairs (33.3%) or medical school permanent deans (27%), compared to 72% of PDs. Conclusion: Females are well-represented as pediatric PDs, but underrepresented in medical school positions with greater authority. Understanding the reasons for this is needed to ensure diverse and representative medical school leadership.